Proactivity-and-consequence-based safety incentive (PCBSI) developed with a fuzzy approach to reduce occupational accidents. (November 2015) - Saracino, Ada; Curcuruto, Matteo; Antonioni, Giacomo; Mariani, Marco Giovanni; Guglielmi, Dina; Spadoni, Gigliola
Graphical abstract: Highlights: A methodology for the assessment of a reward or incentive system based on proactivity and on consequence of potential accidents is proposed. The methodology takes advantage of a tailored Fuzzy Inference System in order to take into account vagueness of human behavior. The methodology has been applied to a case-study through the analysis of some reports from the workers in a process industry. Abstract: This study introduces a new reward system for enhancing safety during work activities, by improving workers' motivation in performance and thereby reducing occupational accidents. The reward system is based on a safety incentive that can be defined by means of two parameters: the worker behavior, which is measured especially in terms of proactivity (namely workers' attitude in reporting potentially hazardous situations) and the consequences that could be avoided thanks to the reporting activity. In doing this, the fuzzy logic theory can be usefully applied, because it offers the opportunity to quantify the two parameters taking into account their vagueness, through the concept of degree of membership and then it also allows to combine them into the final value of the safety incentive through a Fuzzy Inference System (FIS). The model, named "Proactivity-and-Consequence Based Safety Incentive" (PCBSI), has been tested in an Italian chemical plant, with the purpose to evaluate its effectiveness.